Labor prior to cesarean delivery associated with higher post-discharge opioid consumption. - Holly B Ende; Ruth Landau; Naida M Cole; Sara M Burns; Brian T Bateman; Melissa E Bauer; Jessica L Booth; Pamela Flood; Lisa R Leffert; Timothy T Houle; Lawrence C Tsen (PLoS ONE, 2021)
Background Severe acute post-cesarean delivery (CD) pain has been associated with an increased risk for persistent pain and postpartum depression. Identification of women at increased risk for pain can be used to optimize post-cesarean analgesia. The impact of labor prior to CD (intrapartum CD) on acute post-operative pain and opioid use is unclear. We hypothesized that intrapartum CD, which has been associated with both increased inflammation and affective distress related to an unexpected surgical procedure, would result in higher postoperative pain scores and increased opioid intake. Methods This is a secondary analysis of a prospective cohort study examining opioid use up to 2 weeks following CD. Women undergoing CD at six academic medical centers in the United States 9/2014-3/2016 were contacted by phone two weeks following discharge. Participants completed a structured interview that included questions about postoperative pain scores and opioid utilization. They were asked to retrospectively estimate their maximal pain score on an 11-point numeric rating scale at multiple time points, including day of surgery, during hospitalization, immediately after discharge, 1st week, and 2nd week following discharge. Pain scores over time were assessed utilizing a generalized linear mixed-effects model with the patient identifier being a random effect, adjusting for an a priori defined set of confounders. A multivariate negative binomial model was utilized to assess the association between intrapartum CD and opioid utilization after discharge, also adjusting for the same confounders. In the context of non-random prescription distribution, this model was constructed with an offset for the number of tablets dispensed. Results A total of 720 women were enrolled, 392 with and 328 without labor prior to CD. Patients with intrapartum CD were younger, less likely to undergo repeat CD or additional surgical procedures, and more likely to experience a complication of CD. Women with intrapartum CD consumed more opioid tablets following discharge than women without labor (median 20, IQR 10-30 versus 17, IQR 6-30; p = 0.005). This association persisted after adjustment for confounders (incidence rate ratio 1.16, 95% CI 1.05-1.29; p = 0.004). Pain scores on the day of surgery were higher in women with intrapartum CD (difference 0.91, 95% CI 0.52-1.30; adj. p = <0.001) even after adjustment for confounders. Pain scores at other time points were not meaningfully different between the two groups. Conclusion Intrapartum CD is associated with worse pain on the day of surgery but not other time points. Opioid requirements following discharge were modestly increased following intrapartum CD.